EMG recording of wrist gestures under non-ideal electrode placement for machine control in a manufacturing environment - Jamaludin, Zamberi; Fu @ Hu-Jingwei, Zinvi; Bani Hashim, Ahmad Yusairi; Mohamad, Imran Syakir (Penerbit UTM Press, 2015)
The use of electromyography (EMG) for machine control in a manufacturing environment is challenging due to the inherent electrical noise,and also because machine operators lack anatomy knowledge of muscle location for electrode placement.In this research,an electrode placement scheme is proposed for this user group.An EMG preamp was constructed to observe EMG patterns in lower forearm when electrodes placed by untrained operators are in less optimal locations.Crosstalk was found to be a major issue when electrodes are placed in imperfect locations.The EMG preamplifier was deliberately constructed with low cost components to simulate the increased floor noise due to electrical interferences however from the results,the resulting SNR is acceptable. This study shows that in designing a practical EMG input system,electrode placement is a bigger factor compared to electrical interference.